Three Decades of Consumer Ethnocentrism Research: A Bibliometric Analysis. Issue 1 (January 2023) - Baber, Ruturaj; Upadhyay, Yogesh; Baber, Prerana; Kaurav, Rahul Pratap Singh
Consumer ethnocentric tendencies (CET) is a field of study that has developed a distinct identity among marketing researchers and practitioners. The construct has been used in consumer research for over three decades. This study uses two bibliometric methods to understand consumer ethnocentrism. The analysis reviewed 255 consumer ethnocentrism publications from the last three decades (1989–2020). The co-citation analysis revealed regional development and replication of consumer ethnocentrism research. Following that, the article used co-word analysis to determine the evolution of consumer ethnocentrism study themes. The research findings point to five research themes on consumer ethnocentrism, namely foundations, methods of measuring ethnocentrism, culture, managerial applications, and emerging trends. Finally, the study maps called for a future research agenda on consumer ethnocentrism.